Rethinking Eventual Consistency - Bernstein, Phil; Das, Sudipto (Proceedings of the 2013 ACM SIGMOD International Conference on Management of Data, 2013)
There has been a resurgence of work on replicated, distributed database systems to meet the demands of intermittently-connected clients and of disaster-tolerant databases that span data centers. Many systems weaken the criteria for replica-consistency or isolation, and in some cases add new mechanisms, to improve partition-tolerance, availability, and performance. We present a framework for comparing these criteria and mechanisms, to help architects navigate through this complex design space.